Artrópodes e helmintos parasitos de Cavia aperea Exerleben, 1777 (Rodentia: Caviidae) no sul do Brasil - Krüger, Cristiane Pereira (2006)
Cavia aperea, or popularly preá (Brazilian guinea pig), it is a rodent of diurne habits, mainly in the first hours of the morning and in finish them of the afternoon. They are fed of herbaceous vegetables, they live in tunnels of grassy, being able many times to inhabit agricultural peridomiciliar regions, close to highways of the south region it Brazil, being many adopted times as animal of esteem. With the objective to know the diversity of parasites of this rodent, were examined 33 specimens of Cavia aperea that after abated according to Protective Association of the Animals, they had been brushed and washed for collection of ectoparasites, being after that necropsied and its organs examined in search of endoparasites. The ectoparasites after removed from the animal, were clarified in acetate of metila and mounted in slides with Canada balsam. For collection of the helminths it was examined and one washed separately each organ in sieve, nematodes had been clarified in lactofenol and the members of the Classes Trematoda and Cestoda were prepared according Amato s technique diaphaned in creosote and mounted in slides with Canada balsam. Of the total of examined animals, 100% were infested by lice of the species: Trimenopon hispidum, Gyropus ovalis, Gliricola lindolphoi and G. porcelli, with exception of this, all others are registered for the first time in the State Rio Grande do Sul. Of Siphonaptera, Polygenis (Neopolygenis) atopus it was registered prevalence of 6,1%. The helminthes were: of the Phylum Nematoda - Trichostrongylus sp., Paraspidodera uncinata, Vianella travassosi, Ackertia burgosi and Graphidioides subterraneus; Class Trematoda - Pseudoquinqueserialis caviae, Pseudohippocrepis suttonae n.g. n.sp., Taxorchis caviae and the Cestoda Monoecocestus parcitesticulatus, all cited for the first time in the state Rio Grande do Sul, with exception of Paraspidodera uncinata.